Information and Communication Technologies for Development: Evolution of International Discourse - Z. E. Gomboin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
Information and communication technologies play an increasingly important role in international development theory and practice. However, the international donors’ activities in this field (known as ICT for Development or ICT4D) have yielded mixed results. On the one hand, over a short period of time mobile technologies have ceased to be a privilege of the Global North and have become widespread in developing countries. On the other hand, the development of the ICT sector has had certain negative implications for the Global South. Exponential growth of technological knowledge has widened the gap between the developed and the developing world. Furthermore, new technologies have been introduced and distributed in developing countries very unevenly. Although researchers have various explanations for failures of many ICT4D programs and projects, their poor performance is largely attributable to the intrinsic weaknesses of their conceptualisation which influenced the formulation of goals, expected outcomes and risks assessment. This paper examines the international experience in ICT4D and tracks the evolution of the donors’ stated objectives. The first section outlines conceptual foundations of the ‘ICT for Development’ agenda. The second section examines the evolution of the key donors’ approaches to the ICT sector development in the 1970s and 1980s, which was primarily aimed at promoting economic growth in the Global South. The third section highlights donors’ new policies and priorities outlined in the mid-1990s and focusing predominantly on social factors of development. The final section summarizes the key provisions of critical approaches to ICT4D, which have gained prominence over the last decade. In each section the author examines both conceptual frameworks of the key donors’ policies, and concrete initiatives of international organizations, as well as their financing parameters and modalities. The conclusion is drawn that international actors’ ICT4D efforts resemble a patchwork of isolated programs and initiatives rather than a harmonious structure. Meanwhile, a half-of a century-long history of experimentation with the ICT4D programs shows quite convincingly that the ICT should be regarded only as a means to achieve development goals, and not as an end in itself.